To find the equation to solve for \( x \), we start by using the property that supplementary angles sum up to \( 180^\circ \).
We have:
- \( m\angle TUV = (2x - 25)° \)
- \( m\angle VUW = 110° \)
Since these angles are supplementary, we set up the equation:
\[ m\angle TUV + m\angle VUW = 180° \]
Substituting the expressions we have:
\[ (2x - 25) + 110 = 180 \]
Now, we can simplify this equation:
\[ 2x - 25 + 110 = 180 \]
Combining like terms:
\[ 2x + 85 = 180 \]
This is the equation in simplest terms to solve for \( x \). Therefore, we have:
\[ 2x + 85 = 180 \]